Konsep Islamic Worldview dan Implementasinya dalam Kehidupan Modern - Mujahid, Kasori; Miftahurohman, Miftahurohman (Lembaga Yasin AlSys, 2025)
The concept of Islamic worldview and its implications in modern life. Islam is not only a religion, but also a comprehensive guide that covers the spiritual, social, economic and political aspects of daily life. This concept emphasizes the importance of integrating Islamic teachings into every aspect of an individual Muslim's life. The concept of Islam as a way of life with regard to its views and implications in modern life. This study explores the main aspects of the concept of Islam that permeate the daily lives of Muslims and how it can be applied in the context of modern life. By combining the views of religion and modern life, this article aims to provide an indepth understanding of how Islam can guide life in the contemporary era.